Working on the edge: changes in the content and delivery of social care. Issue 4 (22nd October 2019) - Moriarty, Jo; Manthorpe, Jill; Harris, Jess
Abstract : Purpose: The purpose of this paper is to describe some of the changes to the content and delivery of care work in the context of developments in the wider labour market. Design/methodology/approach: A total of 240 interviews with social care practitioners and managers were undertaken at Time 1 (T1) (2009–2012) and Time 2 (T2) (2011–2014) in four local council sites in England. A final round of interviews (T3) with managers ( n =60) and staff ( n =60) took place between 2015 and 2018. Findings: The way in which many workers found meaning and satisfaction within their work was an important way by which many of them tempered dissatisfaction with pay, status and working conditions. Some workers used the concepts of ethical practice and vocation to differentiate themselves from other workers and organisations whom they considered lack these qualities and from what they saw as a wider societal perception that their work was unskilled and unfulfilling. Research limitations/implications: The interview data may not be generalisable or totally representative of care staff. Those employers who agreed to participate may have been more committed to workforce development and valued their staff more highly. Nonetheless, data were sector wide and there were sizeable numbers of participants. Practical implications: Pride and job satisfaction are important aspects of job satisfaction in care work and could be fostered in care services and by older people. Social implications: Negative perceptions of care work within society may act as a barrier to recruitment and retention. Older people might help raise the positive profile of care work. Originality/value: This is a unique data set from which to document long-term determinants of job satisfaction in care work.